Methane Extraction and Resource Utilization Based on Multisource Data Fusion - Wensheng Chen; Zhongliang Lu (Advances in Materials Science and Engineering)
Gas clusters can reprove the sewage ability of flame-permeability char joint, but the interaction motion between proposed vapor molecules and gasoline-confine charcoal during the wind enema advance is still unclear. For this consideration, supported by the surface assimilation figure of qualifier-enclose char, the magnificent orthodox whole Monte Carlo (GCMC) manner was interesting to ponder the elution conduct of CH4 in the wind-confine charcoal configuration after the farding bag of N2/CO2 under distinct enema stamp. The clockwork of N2/C advances the elution of CH4 in charcoal. The examination ensues showed the following: (1) Compared with the enema of N2, the gasoline-restrain charcoal has more familiar CH4 molecules after CO2 enema, and the constituting force of the CH4-CO2 system is everywhere more humble than that of the CH4-N2 system, the former is more fix. (2) In the same enema pattern, obtained with the CH4-N2 system, the CH4 grout indicated more regular distribution in the CH4-CO2 system. CH4 heptane is more active, the expansion cooperation of CH4 in the CH4-CO2 system is more, and the effect of CO2 in promoting the elution of CH4 is better. (3) After CO2/N2 is interjected into the fart-hold charcoal construction, as the enema compression extension, the referring concentrations of CO2, N2, and CH4 in the coping wax, the opposite to major of CH4 in the CH4-CO2 system is the zenith everywhere. In the CH4—N2 system, the opposite to major of CO2 in the CH4 and CH4—CO2 system is in the centric, and the opposite to major of N2 in the CH4—N2 system is the lowermost. (4) The reasonably enema affliction for N2 to raise CH4 elution is between 2 and 4 MPa, and CO2 is honest to advance CH4 elution. The enema urgency is between 3 and 4 MPa. Based on this data, methane extraction and resource utilization can be improved to a certain extent. The result has shown that the inquiry effect can condition speculative uphold for the research studies of char cicatrix petrol enema irritation technology.